2019
DOI: 10.2134/jeq2018.05.0207
|View full text |Cite
|
Sign up to set email alerts
|

Duckweed as an Agricultural Amendment: Nitrogen Mineralization, Leaching, and Sorghum Uptake

Abstract: Excessive N and P in surface waters can promote eutrophication (algae-dominated, low-O 2 waters), which decreases water quality and aquatic life. Duckweed (Lemnaceae), a floating aquatic plant, rapidly absorbs N and P from water and its composition shows strong potential as a soil amendment. Therefore, it may be used to transfer N and P from eutrophic water bodies to agricultural fields. In this work, dried duckweed was incorporated into agricultural soil in microcosm, column, and field tests to evaluate biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 8 publications
(9 reference statements)
1
11
0
Order By: Relevance
“…Some studies have found duckweed to be viable as fertilizer. One study that incorporated dry duckweed into agricultural fields found the application to be a sustainable source of N and P during their research (Kreider et al, 2019). Similarly, one research study found that duckweed mixed with fertilizer may be comparable to commercial fertilizer (F. Pulido, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found duckweed to be viable as fertilizer. One study that incorporated dry duckweed into agricultural fields found the application to be a sustainable source of N and P during their research (Kreider et al, 2019). Similarly, one research study found that duckweed mixed with fertilizer may be comparable to commercial fertilizer (F. Pulido, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy duckweed can be compared to commercial fertilizer in terms of nitrogen availability and used to increase plant productivity in a sustainable manner. Kreider, et al [316] incorporated dried duckweed into the soil in microcosm, column and field trials and compared it to compost, diammonium phosphate (DAP) and amendment-free soil (control) in terms of biological nitrogen cycling, nutrient retention and crop yield. According to the results, duckweed N mineralization (25 ± 13%) was higher than that of compost (11 ± 12%) and lower than that of DAP (107 ± 21%) in microcosm tests.…”
Section: Fertigationmentioning
confidence: 99%
“…Table 1 shows the chemical composition of NPK fertilizer used to prepare agricultural run-off. Numerous studies has suggested and reported the utilization of duckweed specie for phytoremediation of wastewaters rich in nutrients like nitrates and phosphates which includes municipal wastewater and agricultural runoff (El-Kheir et al, 2007;Landesman et al, 2010;Ceschin et al, 2019;Kreider et al, 2019). Agricultural runoff was selected in this study for analyzing the potential of Spirodela polyrhiza to remove nitrates andphosphates from wastewater.…”
Section: Phytoremediation Of Agricultural Runoff By Spirodela Polyrhizamentioning
confidence: 99%